KORELASI KADAR GLUKOSA DENGAN NILAI PH PADA TROMBOSIT KONSENTRAT DALAM BERBAGAI WAKTU PENGOLAHAN SELAMA PENYIMPANAN DI RSUP DR SARDJITO YOGYAKARTA - , AN NISSA YOERIZTA RATU; , Dr.Teguh Triyono,M.Kes,Sp.PK ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Quality control of platelet concentrate product is conducted to determnine the profile of Platelet Storage Lesion (PSL) during storage. One of the parameters of PSL is glucose level and pH value. Glucose and lactate were directly involved in the platelet metabolism in generating energy, while the pH is a result of changes in lactate levels. Declining level of glucose and pH values can significantly affect the quality of platelet concentrate. The purpose of this study was to determine the correlation between blood glucose level and pH value during storage day 0, day 1, day 3 dan day 6 between the groups with range of processing time 0 hour, 6 hours and 16 hours in platelet concentrate. This was an observational study using cross-sectional design of the study that conducted in the RSUP Dr. Sardjito against 15 sample bags of platelet concemtrate. Samples were stored for 0, 1, 3 and 6 days. The samples were divided into three groups (0 hour, 6 hours and 16 hours processed) were measured with a Beckman Analyzer method GOD-PAP to measure glucose level and Blood Gas Analyzer to measure pH value. By using Pearson Correlation test, r value for the correlation between glucose level and pH value in platelet concentrate seen from the difference in processing time, for the 0 hour processing time the r is 0,737